2006
DOI: 10.1111/j.1468-2508.2006.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Third-Party Interventions into Civil Wars: An Actor-Centric Approach

Abstract: Studies of the decision to intervene into ongoing civil wars should focus on those making the decision, not the conflict. We adopt such an "actor-centric" approach and discuss third-party intervention by emphasizing convergent and divergent interests and the connections between potential interveners, actual interveners, and civil war states. Our model furthermore differentiates between interventions on the side of the government and opposition and takes the sequence of interventions in the same conflict into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(160 citation statements)
references
References 22 publications
6
153
0
1
Order By: Relevance
“…By building a model of conflict expansion and joining we can be confident that we have alleviated some of the selection problems associated with prior work such as the assumption that each conflict has the same probability of expanding. We also make an effort to account for the strategic environment in which states act (Croco and Teo 2005;Findley and Teo 2006). Future research should work to further incorporate how the joining decisions of other states impacts conflict expansion.…”
Section: Discussionmentioning
confidence: 98%
“…By building a model of conflict expansion and joining we can be confident that we have alleviated some of the selection problems associated with prior work such as the assumption that each conflict has the same probability of expanding. We also make an effort to account for the strategic environment in which states act (Croco and Teo 2005;Findley and Teo 2006). Future research should work to further incorporate how the joining decisions of other states impacts conflict expansion.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, the United States Regan, 2002. 37 Yoon, 1997;Michael G. Findley and Tze Kwang Teo, "Rethinking Third-Party Interventions into Civil Wars: An Actor-Centric Approach," The Journal of Politics, Vol. 68, No.…”
Section: Characteristics Of the Target Statementioning
confidence: 99%
“…43 Huth, 1998. 44 Findley and Teo, 2006. 45 Yoon, 1997;Rost and Greig, 2011. 46 Yoon, 1997. 47 Kathman, 2010;Rost and Greig, 2011. 48 Mullenbach and Matthews, 2008. …”
Section: Characteristics Of the Relationship Between The Target Statementioning
confidence: 99%
“…Empirical studies have found that intervention decisions depend upon both the characteristics of the target state (Gent, 2008, Regan, 2000 and the potential interveners (Findley andTeo, 2006, Lemke andRegan, 2004), as well as their shared ties (Saideman, 2001). Empirical studies have found that intervention decisions depend upon both the characteristics of the target state (Gent, 2008, Regan, 2000 and the potential interveners (Findley andTeo, 2006, Lemke andRegan, 2004), as well as their shared ties (Saideman, 2001).…”
Section: The Politics Of Interventionmentioning
confidence: 99%